Identification of feigned maximal shoulder external rotation effort - Chaler, Joaquim; Dvir, Zeevi; Díaz, Urko; Quintana, Salvador; Abril, Àngels; Unyó, Carme; Garreta, Roser (Clinical rehabilitation, 2007)
Objective: To examine the efficiency of the difference between the isokinetic eccentric to concentric strength ratios at high and low velocities (DEC) for identifying feigned maximal shoulder external rotation effort. Background: Previous studies have indicated that the DEC is a powerful identifier of feigned maximal effort. However comparison of maximal versus feigned maximal shoulder external rotation effort has not been undertaken. Due to the high prevalence of rotational shoulder disorders and their chronic ramifications in terms of occupational disability such a study is of specific interest. Design: Maximal and feigned maximal shoulder external rotation isokinetic efforts were compared. Setting: Functional evaluation unit at an occupational rehabilitation centre. Subjects: Seventeen healthy male volunteers aged between 20 and 40 years old. Main measure: Concentric and eccentric isokinetic tests at 30°/s and 120°/s in maximal and feigned maximal experimental conditions. DEC was calculated by subtracting the 30°/s eccentric/concentric peak torque ratios from the 120°/s ones for both experimental conditions. Results: A case-by-case analysis revealed that the DEC scores derived from the feigned effort were significantly greater than their maximal counterparts in all cases, leading to a cut-off value (0.81) which could distinguish between maximal and feigned performances. Conclusions: The findings indicate that the DEC is highly effective in identifying feigned shoulder external rotation effort in normal subjects.